Financial accounting for decision makers - Atrill, Peter 1947-; McLaney, Edward J. 1943- (Pearson, 2022)
"This text provides a comprehensive introduction to financial accounting. It is aimed at students who are not majoring in accounting as well as those who are. Those studying introductory- level financial accounting as part of their course in business, economics, hospitality management, tourism, engineering, or some other area, should find that the text provides complete coverage of the material at the level required. Students who are majoring in accounting should find the text a useful introduction to the main principles, which can serve as a foundation for further study. The main focus of the text is on the ways in which financial statements and financial information can improve the quality of decision making. To ensure that readers understand the practical implications of the subject, there are, throughout the text, numerous illustrative extracts using commentary from company reports, survey data and other sources.